Multidisciplinary Perspectives on Islamic higher Education Curriculum Orientation in Independent Campus Policy (EDUKASIA, 2021)
Curriculum has strategic values in the era of independent campus. This research aims to construct a curriculum based multiple perspectives tends to learners’ preference and diversity in Islamic Higher Education. It’s a mix-method research. Qualitative methods, using naturalistic design with interactive models, while quantitative methods with cross-sectional surveys to determine the level of stakeholder’s understandings and the result of it. The result found that multiple dimensions leads to an eternal-essential closed to the Oneness of God, creativity, capability. The other one refers to instrument; model, knowledge, organization, sequence, need analysis, purpose, value, and stakeholder. Furthermore, the appropriate one tends to an essential-humanistic technologies curriculum in fulfilling for independent campus recognition.